3
$\begingroup$

I have an object traveling along the curve $y=x^2$. $z$ is the distance from the origin and $dz/{dt}=1$ is the rate it's increasing per unit time. At what rate are my $x$ and $y$'s moving at the point (2,4)? In other words what is $dy/dt$ and $dx/dt$.

I've seen the geometry. Found $z$ as the hypotenuse of $x$ and $y$. Also, I infer that $dz=dt $ so they are interchangable. How do I solve this?

$\endgroup$
3
$\begingroup$

Bu definition, $ z = \sqrt{\left(x-0\right)^2 +\left(y-0\right)^2 } = \sqrt{x^2 + y^2}$.

First, let us compute $dx/dt:$

Since $y = x^2$ we can rewrite $z$ in the form $ z = z(x,y) = \sqrt{x^2 + x^4}$. Then by chain rule we have

$$ 1 = \frac{d z}{d t} = \frac{d z}{d x} \,\frac{d x}{d t} \implies \frac{d x}{d t} = \frac{1}{dz/dx} $$

Now,

$$ \frac{d z}{d x} = \left(\sqrt{x^2 + x^4}\right)' =\frac12\, \frac{2x+4x^3}{\sqrt{x^2 + x^4}} = \frac{1+2x^2}{\sqrt{1+x^2}} $$

Substituting $x=2$ into expression above will give you the speed of $x$ at the point $\left(2,4\right)$.

Second, $dy/dt$ can be computed in the same way. Hope you can pick it from here.


Alternatively, one can compute $dy/dt$ in the following manner:

$$ 1 = \frac{d z}{d t} = \frac{d z}{d x} \,\frac{d x}{d t} + \frac{d z}{d y} \,\frac{d y}{d t} = \frac{x}{\sqrt{x^2 + y^2}}\,\frac{d x}{d t} + \frac{y}{\sqrt{x^2 + y^2}}\,\frac{d y}{d t} \\ \implies \frac{d y}{d t} = \frac{\sqrt{x^2 + y^2}}{y} \left( 1 - \frac{x}{\sqrt{x^2 + y^2}}\,\frac{d x}{d t}\right) = \frac{\sqrt{x^2 + y^2}}{y} - \frac{x}{y}\,\frac{d x}{d t}, $$

where $dx/dt$ is known from the first part.

$\endgroup$
1
$\begingroup$

I think this is simpler to understand. By definition

$$z=\sqrt{(x-0)^2+(y-0)^2}=\sqrt{x^2+y^2}$$

Since $y=x^2$

$$z=\sqrt{x^2+x^4}$$

Taking the derivative of this equation using the chain rule gives

$$z^{'}=\left({(x^2+x^4)}^{1/2}\right)^{'}\implies\frac{dz}{dt}=1/2(x^2+x^4)^{1/2-1}(x^2+x^4)^{'}\implies\frac{dz}{dt}=(1/2)(x^2+x^4)^{-1/2}(2x+4x^3)\frac{dx}{dt}$$

Then substitue $\frac{dz}{dt}=1$ and $x=2$ into the previous equation

This gives $1=\frac{1}{2}\frac{1}{\sqrt{20}}(36)\frac{dx}{dt}\implies1=\frac{18}{\sqrt{20}}\frac{dx}{dt}\implies\frac{dx}{dt}=\frac{\sqrt{20}}{18}$

Then take the derivative of $y=x^2$ on both sides to get

$$\frac{dy}{dt}=2x\frac{dx}{dt}$$

Then substitue $x=2$ and $\frac{dx}{dt}=\frac{\sqrt{20}}{18}$ to get your answer.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.